HUBUNGAN ABNORMALITAS EEG DENGAN GAMBARAN HIPOKAMPUS PADA MRI PASIEN EPILEPSI LOBUS TEMPORAL MESIAL - Norma Mediciani, Fitri Octaviana, Jacub Pandelaki, Joedo Prihartono (NEURONA, 2014)
INTRODUCTION MESIAL TEMPORAL LOBE EPILEPSY MTLE IS THE MOST COMMON EPILEPSY SYNDROME IN ADULTS AND OFTEN REFRACTORY IN MEDICAL TREATMENT THE MAGNETIC RESONANCE IMAGING MRI SHOWED HIPPOCAMPAL ATROPHY PRESENT IN 87 PATIENTS WITH MESIAL TEMPORAL LOBE EPILEPSY AND HAVE GOOD RESPONS WITH SURGERY ELECTROENCEPHALOGRAPHY EEG MONITORING IS NEEDED TO FIND ICTAL EEG ALTHOUGH INTERICTAL EEG ALREADY OBTAINED AS ONE OF THE REQUIREMENTS OF EPILEPSY SURGERY FOR LOCALIZE THE EPILEPTIC REGION